The Effect of Public Accountability and Transparency on State Financial Management Mechanism: A Quantitative Method Analysis - Alian Natision; Eddy Bruno Esien; Dwikora Harjo; Redjeki Agoestyowati; Putri Ayu Lestari (Ilomata International Journal of Social Science, 2022)
Since public sector reform initiatives, public accountability and transparency have advanced democracy and good governance on managing state finances. State financial management mechanism involves regional policies and fiscal decentralization trend in the devolution of responsibility for empowerment from central to local units of governments, but the governance face challenges to effectively manage and control the use of public funds that best meet citizen’s needs. This study determines the effect of public accountability and transparency on the management of state finances in Indonesia, as well as the extent to which public accountability and transparency affect the management of state finances. Based on a descriptive quantitative case-oriented research approach, 60 survey interviews are collected and analyzed with multiple linear regression analysis techniques. This study concludes that Public Accountability partially has a significant effect on the Financial Management Mechanism. On the other hand, partially public transparency has no significant effect on the State Financial Management Mechanism. Cumulatively, some aspects of Public Accountability and Transparency have a significant effect on the State Financial Management Mechanism. If unaccountability in decentralised administrative model prevails, problem of ineffective policy output may persist to impair sustainable finance and public values for good governance in times of covid-19 crisis related society.